2012
DOI: 10.1007/s00784-012-0845-7
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy in dentistry: a literature review

Abstract: Oral infections (such as mucosal and endodontic infections, periodontal diseases, caries, and peri-implantitis) are among the specific targets where PDT can be applied. Further long-term clinical studies are necessary in establishing a more specific place of the technique in the field of dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
165
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(190 citation statements)
references
References 110 publications
(135 reference statements)
1
165
0
13
Order By: Relevance
“…This study indicated that S. mutans biofilms are susceptible to Violet-blue light with an exposure time of 5 mins suggesting that S. mutans contains an endogenous photosensitizer. The combination of a specific photosensitizer with a light source of appropriate wavelength, availability of oxygen and also the type of a particular organism or a group of microorganisms, plays a vital role in the application of photodynamic therapy [14,18,37]. The mechanism behind photoinactivation of S. mutans is not known, and to our knowledge only one study has used Violet-blue light with no photosensitizer on S. mutans biofilms [6].…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated that S. mutans biofilms are susceptible to Violet-blue light with an exposure time of 5 mins suggesting that S. mutans contains an endogenous photosensitizer. The combination of a specific photosensitizer with a light source of appropriate wavelength, availability of oxygen and also the type of a particular organism or a group of microorganisms, plays a vital role in the application of photodynamic therapy [14,18,37]. The mechanism behind photoinactivation of S. mutans is not known, and to our knowledge only one study has used Violet-blue light with no photosensitizer on S. mutans biofilms [6].…”
Section: Discussionmentioning
confidence: 99%
“…Meisel and Kocher 20 showed that the use of photosensitizing dyes and their activation with laser beams might result in the destruction of pathogens responsible for periodontal diseases and peri-implantitis. Gursoy et al 39 suggested that PDT might be an appropriate tool in superficial and local infections, and although it cannot be an alternative for antimicrobial agents, it might facilitate the treatment of oral infections. Therefore, considering the results of studies on the effect of PDT on periodontal pathogens, periodontal infections and periimplantitis, in the present study PDT was applied in the test group and its effects were compared with those of laser therapy (LT) alone in the control group.…”
Section: Effectiveness Of Photodynamic Therapy In Treatment Of Peri-imentioning
confidence: 99%
“…30 Photodynamic therapy has also been used to disinfect caries dentin before restoration, disinfecting oral tissues before or during surgical procedures, treating denture stomatitis, and treating oral candidiasis in immunocompromised patients. 31,32 With regard to bacteria involved in dental caries, Burns et al 33 showed that tolonium chloride (25 g/mL)…”
Section: Photodynamic Therapy In Dentistrymentioning
confidence: 99%